The approaches of conflict resolution depicted in sanskrit hitopadeśa - Dhammaloka, J. (University of Jaffna, 2012)
The conflicts are general features of the active societies. Human beings have used many resolution methods to conciliate them. Therefore, they can be divided into two main groups as Traditional approach and Modern approach. The Sanskrit Hitopadeśa which was used to teach ‘nītiśāstra’ has also given attention to maintain peace in the society and to conciliate the conflicts. Therefore, the objective of this research is to examine the conflict resolution methods of the Hitopadeśa. To achieve this, studying literary resources (ancient and modern) is used as the methodology. The central idea of it is that if there is a conflict somewhere because of certain cause certainly there is a resolution for it. Therefore, the solution must be given to that first cause. Hence, to resolve the conflicts the Hitopadeśa recommends many methods and techniques. It describes the diplomatic and human relations in the general society, using the jungle as a background, animals as the characters and stories as the medium of the teachings. The traditional approach is the main approach recommended by Hitopadeśa very often but modern approach also can be seen in several times. Hitopadeśa has used many stories to prove it. But, indeed, the same method can’t be applied for all conflicts. Therefore, Hitopadeśa recommends some other approaches also. Negotiation, facts-finding, conciliation, mediation, facilitation, arbitration are some of them which included the modern approach. The technique of mediation is the other method, it recommends frequently. The qualifications of the mediators, specially, of the diplomatists are also described deeply. Hitopadeśa describes many harmonizations called ‘sandhi’ in the ending of it and it appreciates the ‘upahāra sandhi.’ In conclusion, it is clear that the Hitopadeśa has considered about the conflict resolution in many ways.
Keywords: Hitopadeśa; Harmonizations